(untitled) (Daffodil International University Journal of Science and Technology, 2012)
Industrial system involves physical and chemical treatment as well as biological processes. Therefore, waste treatment systems such as the industrial effluents depend on the activities of communities of living organism. In this study, an attempt was made on the identification of the bacterial population involved in different industrial effluents. A total of thirty bacterial strains were isolated from glass, textile and pharmaceutical effluent samples on L.B. agar plates. A few, however, were re-cultured on other recommended media for verification of diagnostic characteristics. Maximum numbers of bacterial species were isolated from textile effluent. The results showed that a gramnegative bacillus with a yellow pigment was considered as a major group of the population. These are also being used in different waste water and metal treatment plants all over the world. Keywords: Bacterial identification; industrial effluents; gram negative. DOI: http://dx.doi.org/10.3329/diujst.v7i1.9644 Daffodil International University Journal of Science and Technology Vol.7(1) 2012 28-33